A motorcycle courier in the Great War the illustrated edition - Watson, William Henry Lowe 1891-1932; Carruthers, Bob 1960- (Military history from primary sources, 2013)
"'The right flank of the 13th has been badly turned. Most of our officers have been killed. Some companies of the K.O.S.B. are endeavouring to cover our retreat'...Despatch, Battle of Mons; W.H.L. Watson was a British Army, motorcycle despatch rider in World War I. He saw active service during the key battles of 1914 and early 1915. Watson and his colleagues formed part of the Royal Engineers Signal Service and these riders were originally volunteers, some of whom supplied their own machines. This amazing account details the experiences of these brave young men and provides a unique primary source account of life at the sharp end during the titanic struggles fought out in Northern France and Belgium. Richly illustrated with contemporary photographs and maps, this evocative description of the actions of the British Expeditionary Force is a key source and is essential reading for anyone interested in the history of the Great War. Highly detailed, but nonetheless accessible this superb volume is greatly recommended for serious enthusiasts and casual readers alike. Eyewitness accounts of these early clashes are comparatively rare and Watson's wonderfully personal account provides a rare insight from an unusual perspective"...From publisher's website